PROJECT BASED LEARNING IN NATURAL AND SOCIAL SCIENCE LEARNING: IMPROVING CRITICAL THINKING SKILLS AND SELF EFFICACY OF MADRASAH IBTIDAIYAH STUDENTS - Eva Luthfi Fakhru Ahsani; Ade Aini Fitriyaningsih (PD PGMI se Indonesia, 2025)
This study aims to describe the improvement of students' critical thinking skills and self- efficacy through the implementation of project-based learning in the independent curriculum for fifth-grade students. It is a field research study using a quantitative approach. The research method employed is pre-experimental with a one-group pretest-posttest design. The subjects of this study are the teachers and fifth-grade students of MI NU Tarbiyatul Islam. The results of the study show that the implementation of the project-based learning model involves several phases, including determining the project, designing the steps to complete the project, scheduling the project implementation, carrying out the project, preparing reports and presenting project results, and evaluating both the process and outcomes of the project. Students' critical thinking skills in science learning using the project-based learning model showed a significant difference between pretest and posttest scores in both critical thinking skills and self-efficacy. This is evidenced by the hypothesis test results, where the value of t-count < t-table = 0.00 < 0.05. This learning model has the potential to serve as a reference in the formulation of more contextual and adaptive educational policies.